The influence of salespeople training on the customer satisfaction of a network’s vehicle dealers by structural equations modeling - Tomoyose, Fábio Hiroshi; Faria, Ana Cristina de; Gaspar, Marcos Antonio; Kubo, Edson Keyso de Miranda (Contextus - Revista Contemporânea de Economia e Gestão, 2017)
This study aimed to verify the influence of salespeople training of vehicle dealers in Rio de Janeiro state on the customers satisfaction of an automaker. We adopted the secondary data treatment and the Structural Equation Modeling, with partial least squares estimation, in a sample of 130 dealers, 936 respondents to the satisfaction survey and the analysis of training performance of 1,158 vendors. It was concluded that the salespeople training of vehicle dealers plays a strategic role in creating value to the customer and generating competitive advantage, even though it has no direct relation with the customer satisfaction. Through the presented results, it can be affirmed that the trainings carried out by the vendors are directly linked to the perceptions of the clients about the quality in services offered by the automaker and its concessionaire network. By the presented results, it can be said that salespeople trainings are directly linked to the customer perceptions about service quality offered by the automaker and its dealers network.